HUBUNGAN KESEPIAN DENGAN TINGKAT DEPRESI PADA LANSIA DI PANTI GRIYA LANSIA HUSNUL KHATIMAH WAJAK MALANG: The Relationship Between Loneliness and The Level of Depression in The Elderly at The Griya Elderly Home Husnul Khatimah Wajak Malang - Theresia Beto Suku Rere; Yanti Rosdiana; Wahidyanti Rahayu H (Forind Press, 2024)
Loneliness is often a common psychological problem in the elderly, especially when they are separated from their family, lose their spouse, and have difficulty living independently. This adverse impact can affect the psychosocial and psychological well-being of the elderly, causing depression. This study aims to determine the relationship between loneliness and the level of depression in the elderly at Griya Lansia Husnul Khatimah Wajak Malang. The research design used Cross sectional. The population in the study was physically and mentally healthy elderly in the orphanage as many as 67 people with simple purposive sampling technique obtained a research sample of 58 people. The independent variable is loneliness, the dependent variable is the level of depression. The instruments used were the University of California Los Angeles (UCLA) Version 3 questionnaire and the Geriatric Depression Scale (GDS) questionnaire sheet. The data analysis method used was Fisher's Exact Test (P value <0.05). The results showed that most respondents (56.8%) had moderate loneliness and almost half of the respondents (36.2%) had severe depression. Fisher's Exact Test results obtained P value (<0.05) that there is a relationship between loneliness and the level of depression in the elderly at Griya Lansia Husnul Khatimah Wajak Malang. Future researchers are expected to conduct more in-depth research that can affect loneliness and depression levels such as biological, physical, and psychological factors.